Pengaruh Self Eficacy dan Kepercayaan Diri terhadap Motivasi Belajar dan Motivasi Berprestasi Mahasiswa yang Bekerja Paruh Waktu - Nopen, Pikri (Journal of Islamic Education Counseling, 2025)
Self-confidence is closely related to the philosophy of self-fulfilling prophesy and self-efficacy. If a person believes in the abilities that exist in him, then he will also feel confident in carrying out his activities. The method used is systematic literature review. The purpose of this systematic literature review is to know and understand self-efficacy (self-belief) and self-confidence in students who work full-time. Research articles were obtained from three databases, namely sciencedirect, SAGE Journal and Garuda. Inclusion criteria for research articles from 2018-2023. From 5,820 research articles, 8 articles were reviewed that met all inclusion criteria and objectives of this literature review. Based on the results of this article review, self-efficacy and self-confidence have a tremendous impact on the lives of students, especially those who work full-time. Keywords: self efficacy, self confidence, students, working full time.